The culture of migration in the Brazilian municipality of Governador Valadares: an analysis of the networks of meanings and their impacts on the international migration flows (Revista Espinhaço, 2017)
During the 2000’s Brazil and the United States have undergone economic shocks (positive and negative). Historical migration flows from the Brazilian municipality of Governador Valadares (GV) towards the US, however, remained unaffected. One of the factors explaining the stability of this migration system is the role played by the return migrant and the called ‘Culture of Migration’. This study focuses on this second factor, proposing a cognitive analytical model on the culture of migration and, more specifically, on the analysis of social representations that are associated to migratory behaviors through the analysis of the networks of meanings. For that, we used data from 1226 respondents and their evocations about international migration for the creation of the nested networks.The general network of meanings presented an intermediation mainly managed by the objects Better Life, Money, Work and Opportunity. The analysis of the possible differentials of gender, age groups and international migratory experience at home pointed out that, although there are distinctions already observed in other works, they were not significant to be classified as cultural subsets within this cultural phenomenon. This suggests that the migratory culture is widespread so that all groups perceive international migration in the same way.
Keywords: Culture of migration; networks of meanings; international migration; Governador Valadares; United States